The Communication Strategy of Cireundeu Indigenous Community in Preserving Food Security and Developing Ecotourism - As’adillah Sudrajat, Abijar; Wilda Riva Fadhilah; Sansa Bunga Agista; Willy Putra; Putri Ayu Salamah; Wina Nurhayati Praja (LPPM Stikosa - AWS, 2024)
Optimizing Food Security Maintenance: Utilizing Natural Resources at the Local Level, Illustrated by the Cireundeu Indigenous Village's Commitment to Local Wisdom in Safeguarding Food Security. As an indigenous community, the Cireundeu people employ specific communication methods to preserve and uphold their food security principles, making them a focal point for ecotourism. This research aims to understand how the Cireundeu indigenous community comprehends and implements the concept of food security. Additionally, it investigates how this concept is communicated to the younger generation to ensure sustainability and serve as an attraction for ecotourism. The research design employs a qualitative approach and ethnographic methods, with data collection techniques including observation and semi-structured interviews. The findings describe four food security concepts within the Cireundeu Indigenous Village and outline four communication strategies employed to sustain these principles and attract ecotourism. In conclusion, the research reveals that through food security concepts and communication traditions, the Cireundeu indigenous community is dedicated to ensuring adequate access to food security for all members and promoting ecotourism appeal.